2011
DOI: 10.2147/jmdh.s20075
|View full text |Cite
|
Sign up to set email alerts
|

Construct validity of the Moral Development Scale for Professionals (MDSP)

Abstract: The aim of this study was to investigate the construct validity of the Moral Development Scale for Professionals (MDSP) using structural equation modeling. The instrument is a 12-item self-report instrument, developed in the Scandinavian cultural context and based on Kohlberg’s theory. A hypothesized simplex structure model underlying the MDSP was tested through structural equation modeling. Validity was also tested as the proportion of respondents older than 20 years that reached the highest moral level, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In particular, moral development demonstrated a significant increase in stages 5 and 6. According to the moral development theory [ 56 ], individuals reach the upper moral level after passing through lower moral stages. Stages 3 and 4 belong to level 2 morality, whereas stages 5 and 6 are level 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, moral development demonstrated a significant increase in stages 5 and 6. According to the moral development theory [ 56 ], individuals reach the upper moral level after passing through lower moral stages. Stages 3 and 4 belong to level 2 morality, whereas stages 5 and 6 are level 3.…”
Section: Resultsmentioning
confidence: 99%
“…Moral Development Scale for Professionals (MDSP) [ 56 ]. This 12-item scale helps assess students’ endorsement of moral and ethical values before and after attending the program.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, a previous study demonstrated that people in the Western culture used the conversation and opinion sharing with their friends, whereas people in the Confucian culture such as Koreans and Chinese used SNS to maintain offline relationship. (12,13) In this study, the participants shared mainly "pictures of myself " with their friends, who already have established relationships to seek social support from or via SNS. However, when they upload more personal and sensitive information, consequently invasion of privacy may be occurred.…”
Section: Discussionmentioning
confidence: 99%
“…(12) This scale asks to consider six statements (e.g., "I do not care who sees the information available on SNS") related to privacy of social network websites. A higher score indicates a higher degree of discreet attitudes toward privacy in SNS.…”
Section: Instrumentsmentioning
confidence: 99%
“…In this study, cognitive moral development defined as the individuals' ability in determining difference between right and wrong that affect their actions upon others. For cognitive moral development, Moral Development Scale for Professionals by Soderhamn, Bjornestad, Skisland and Cliffordson (2011) consist of 12 items that measure the Kohlberg's Cognitive Moral Development Stages. Thus, this instrument was employed to measure the variables.…”
Section: Cognitive Moral Developmentmentioning
confidence: 99%